MUSCULOSKELETAL ISSUES AMONG DENTAL MEDICINE STUDENTS: A CROSS-SECTIONAL STUDY - Cristina Iordache; Ana Maria Fătu; Mădălina Miftode; Codrina Ancuța; Norina Forna (Romanian Journal of Oral Rehabilitation, 2016)
The burden of work-related musculoskeletal pathology among dental professionals is widely recognized, particularly associated with specific risk factors in routine practice. Aim of the study: The main objective of our study was to evaluate musculoskeletal issues in students in dentistry based on their participation in different levels of professional activities, and to identify potential risk factors. Material and methods: We performed a cross-sectional study in 100 consecutive students attending the School of Dentistry, “Grigore T. Popa” University of Medicine and Pharmacy Iasi, classified in two main groups: 50 students in their first and second year of study, not engaged in specific dental work (group A) and 50 students in their third to sixth year, already performing professional activities in patient (group B). A predefined questionnaire survey was applied in all students, including general data, risk factors for musculoskeletal problems, and information on pain (vertebral, hand) and muscle spasm as main musculoskeletal complains potentially related to their professional doings. Conclusions: Ergonomic postures adopted by the student / dentist in routine practice as well as ergonomic dental instruments are usually associated with less vertebral (lumbar spine) and hand pathology. Ergonomic principles must be applied in routine dental practice and the student educated about prevention of musculoskeletal pathology.